2017
DOI: 10.5511/plantbiotechnology.16.1231b
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of blueberry shoot tips derived from in vitro and current shoots using D cryo-plate technique

Abstract: Cryopreservation is an important tool for long-term storage of plant germplasm that is currently used for plant germplasm storage at many institutes worldwide. Recently, novel cryogenic procedures (V and D cryo-plate methods) have been developed. In this study, the most suitable conditions for preserving blueberry shoot tips derived from in vitro and current shoots using the D cryo-plate method were investigated. The D cryo-plate method has advantages such as higher regrowth after cryopreservation and a more u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…For non-cryopreserved seeds, the maximum regrowth percentage is 82.1 %, and the highest regrowth frequency of cryopreserved seeds was obtained after 60 min dehydration (57.8 %; Table 1). Due to the different dehydration time treatments, 60 min of dehydration time gave the highest germination and regrowth results for cryopreserved seeds, the same as Salma et al [48] and Dhungana et al [49], which reported high germination percentages of date palm proembryogenic and blueberry shoot observed after 60 min dehydration by using D cryo-plate technique. The different exposure times of plant materials to PVS2 solution were designed to cover the interval of normal usage at 0, 30, 60, 90, and 120 min.…”
Section: Dehydration Cryo-plate Technique (D Cryo-plate)supporting
confidence: 59%
“…For non-cryopreserved seeds, the maximum regrowth percentage is 82.1 %, and the highest regrowth frequency of cryopreserved seeds was obtained after 60 min dehydration (57.8 %; Table 1). Due to the different dehydration time treatments, 60 min of dehydration time gave the highest germination and regrowth results for cryopreserved seeds, the same as Salma et al [48] and Dhungana et al [49], which reported high germination percentages of date palm proembryogenic and blueberry shoot observed after 60 min dehydration by using D cryo-plate technique. The different exposure times of plant materials to PVS2 solution were designed to cover the interval of normal usage at 0, 30, 60, 90, and 120 min.…”
Section: Dehydration Cryo-plate Technique (D Cryo-plate)supporting
confidence: 59%
“…Highest regrowth was recorded in the cultivar Blugold (100%) using in vitro grown shoot tips which was significantly higher than current shoot tips (17.2%), followed by Festival (96.9% in in vitro shoot tips). In cultivars viz., climax, Magnolia and Weymouth no significant difference was observed in regrowth percentage of in vitro and current shoot tips showing the influence of varietal response in cryopreservation (Dhungana et al, 2017).…”
Section: Cryoplates Methodsmentioning
confidence: 77%
“…For preserving the shoot tips of in vitro and field grown blueberries, Dhungana et al, (2017) have attempted D-cryoplate method. The ideal explant, preculture treatments, loading and desiccation period were investigated and found that shoot tips from in vitro grown plants had better survival (86.7%) than shoot tips from field grown current shoots (59.7%).…”
Section: Cryoplates Methodsmentioning
confidence: 99%
“…Cryopreservation emerges as the premier method for safeguarding germplasm over extended durations, especially considering the arduous process of vegetative propagation required for preserving clonal genotypes in numerous fruit crops [95,96]. This technique offers the ability to store plant material in an unaltered state indefinitely, shielding it from contamination while demanding minimal upkeep [95].…”
Section: Blueberry Tissue Culture Innovationsmentioning
confidence: 99%